Problematika Formulasi Latar Belakang Dalam Penelitian Tindakan Kelas: A Systematic Literature Review - Silvia Santi Ekik Prayustin; Yusi Nisa Adila; Fadilatul Firdausiah; Safira Annisa Rahman; Imron Fauzi (Advances In Education Journal, 2026)
This study aims to analyze the challenges of formulating the background in classroom action research (CAR), particularly regarding argumentative and methodological gaps in the development of the research rationale. This study employs a Systematic Literature Review (SLR) approach by examining scholarly articles from reputable journals that discuss CAR practices, the quality of academic writing, and the construction of educational research arguments. The literature search was conducted through the Scopus, ScienceDirect, ERIC, and Google Scholar databases for the years 2015–2025, resulting in a final total of 20 articles that met the inclusion criteria and were analyzed using the PRISMA guidelines. The results of the literature synthesis indicate that the background of PTK is still formulated descriptively, lacks a clear identification of research gaps, is poorly integrated with theoretical reviews and prior research, and does not demonstrate a clear connection between the problem, actions, and research design. These conditions give rise to two primary gaps: an argumentative gap and a methodological gap. The novelty of this study lies in the conceptualization of these two gaps as an integrative analytical framework for systematically evaluating the quality of the formulation of the PTK background.